(untitled) (Environment & Health, 2016)
We determined the quantitative indices of the impact of non-standard drinking water on the circulation system diseases in the Kherson’s population using a highly mineralized water from the centralized drinking water supply system. Methods and materials. We studied the impact of mineralized tap drinking water from the underground sources in Kherson on the morbidity of the circulation system diseases. The water, using by the population, includes above-standard levels of hardness salts, dry residue, chlorides and sulfates. The values of these parameters in drinking water exceed the MAC 2 times, and 3-4 times in the Suvorov district of the city. Chernihiv was taken as a control, there were no deviations from the standard there. All the newly registered cases of the circulation system diseases and separate nosologies for ten years period (2004-2013) in these cities were a subject of the retrospective epidemiological surveillance by the cohorts’ method. Results. Primary morbidity analysis showed a significant difference of the circulation system diseases levels in the studied settlement in comparison with the control one (p